Factors influence participation of rural women in PADZEY project in Yemen - Al-Areqi, Belqes Mutahar Abdulwahid; Othman, Jamilah; Abu Samah, Bahaman (Universiti Putra Malaysia, 2009)
This study was designed to determine the factors influencing the participation of rural women in PADZEY project in Yemen. The research employed quantitative data collection through personal interviews by a questionnaire. 172 rural women were randomly selected as respondents from three districts in Tiaz government, Descriptive statistic and person correlations were used to analyses the data. The main objectives of this study were to measure the level of participation and the correlation ship between demographic factors, knowledge, skills, attitude, and level of participation. The findings showed that the level participation of rural women in PADZEY project is low. In addition, moderate level of rural women’s knowledge in PADZEY project, skills of livestock production, and attitude towards PADZEY project. Level of rural women’s participation in PADZEY project is significantly and correlated with monthly income, knowledge in PADZEY project, skills of livestock production, and attitude towards PADZEY project, only number of family member and experience is no significantly with participation.